Effect of carbon nanotubes on the curing dynamics and network formation of cyanate ester resin - Yue Lin; Corinne A. Stone; Steve J. Shaw; Mo Song (2013)
The effect of a pristine carbon nanotube (CNT), and three functionalised carbon nanotubes on the curing dynamics and network formation of a cyanate ester resin (CY), was investigated by means of differential scanning calorimetry (DSC), modulated temperature differential scanning calorimetry (MTDSC), field emission gun scanning electron microscopy (FEGSEM), Fourier transform infrared (FTIR) and Raman spectroscopies. Incorporation of the various carbon nanotubes showed different accelerating effects on cure of the CY. Addition of the pristine multi-walled carbon nanotube (MWCNT) did not show a prominent accelerating effect, whilst a carboxyl group functionalised multi-wall nanotube (MWCNT-COOH) displayed the greatest accelerating effect. For a hydroxyl group functionalised multi-walled carbon nanotube (MWCNT-OH)/CY system, the most pronounced accelerating effect was observed when 1 wt% to 2 wt% MWCNT-OH was added. Nano-scale dispersion of both the pristine and the functionalised multi-walled carbon nanotubes in the CY matrix was observed by using FEG-SEM. In contrast, micro-scale aggregation happened in a SWCNT-OH/CY system. The FTIR spectra monitored the formation of triazine rings in the CY and its composites with CNTs. The FTIR results indicated that the CNTs reacted with the cyanate groups of the CY to form oxime C=N-O bonds. The up-shifting of the bands for CNTs in Raman spectra confirmed nano-scale dispersion of MWCNTs in the CY matrix and strong interaction between the MWCNTs and the CY.